2017
DOI: 10.4085/1062-6050-52.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Recovery Patterns After Sport-Related Concussion

Abstract: Context: Clinicians sometimes treat concussed individuals who have amnesia, loss of consciousness (LOC), a concussion history, or certain symptom types more conservatively, but it is unclear whether recovery patterns differ in individuals with these characteristics. Objective: To determine whether (1) amnesia, LOC, and concussion history influence the acute recovery of symptoms, cognition, and balance; and (2) cognition and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 43 publications
(69 reference statements)
2
32
0
Order By: Relevance
“…Because clinicians using an EMR have existing data, retrospective studies are recommended as a first step. One retrospective approach is a case-control study 31 (Figure 1 and Table 2), in which the goal is to establish a relationship between exposures (ie, intervention, characteristic, or experience 32 ) and an outcome. Another approach is the cross-sectional study design 33 (Figure 2 and Table 2), which compares multiple groups at 1 point in time.…”
Section: A Call To Action: Using Emrs To Conduct Research At the Poinmentioning
confidence: 99%
See 3 more Smart Citations
“…Because clinicians using an EMR have existing data, retrospective studies are recommended as a first step. One retrospective approach is a case-control study 31 (Figure 1 and Table 2), in which the goal is to establish a relationship between exposures (ie, intervention, characteristic, or experience 32 ) and an outcome. Another approach is the cross-sectional study design 33 (Figure 2 and Table 2), which compares multiple groups at 1 point in time.…”
Section: A Call To Action: Using Emrs To Conduct Research At the Poinmentioning
confidence: 99%
“…Teel et al 31 recently investigated the effect of several acute variables on concussion-recovery patterns in collegiate and high school athletes. Variables were collected at baseline (eg, concussion history) or at initial injury evaluation (eg, amnesia, loss of consciousness) by an AT participating in the Concussion Prevention Initiative.…”
Section: Example Of An Observational Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The 2017 Berlin Consensus Statement supports removing athletes from sport or high-intensity cognitive activity in the acute period of one to two days post-injury, 2 which reflects initial recovery in motor coordination and balance. 26,42 The need to remove patients from activity has been supported by two recent prospective studies. An observational study of children and adolescents between 11 and 19 years of age found an association between the time lapse from injury to the beginning of physical and cognitive rest and the time taken to recovery, which was defined as academic activity at pre-concussion levels.…”
Section: Implications For Concussion Management and Return To Sport Pmentioning
confidence: 99%